Moving Beyond Traditional Knowledge Management: A Demand-Based Approach - Moussa, Chihab Ben (Journal of Knowledge Management Practice, 2009)
Large numbers of organizations invested heavily in Knowledge Management (KM) projects with the aim of increasing responsiveness and innovation, saving costs, supporting decision making, facilitating collaboration, and enhancing overall competitive position. However studies show that a large proportion of KM initiatives fail. Yet little detailed attention has been paid to why those initiatives run into difficulties, and how the failure of the often costly KM project could be avoided. The present study showed through a comparative study of two case studies of KM implementation, the need for a new approach to knowledge management where both the supply side and demand side of knowledge are addressed i.e. individuals’ needs will work in an integrated way.
Keywords: Knowledge management; Supply-driven approach; Demand-driven approach; Activity theory